PATH-21. THE SINGLE-CELL PATHOLOGY LANDSCAPE OF PEDIATRIC GLIOMA. (12th November 2021) - Messiaen, Julie; Nasari, Pouya; Van Herck, Yannick; Verhaaren, Ben; Sebastian, Ivey; Milli, Giorgia; Bosisio, francesca; Pey, Jon; De Vleeschouwer, Steven; De Vloo, Philippe; Depreitere, Bart; Vanden Bempt, Isabelle; et al.
Abstract: High-grade glioma are the main cause of cancer-related death in children. Despite extensive research, their prognosis remains poor with very few treatment options. This can be attributed to the highly heterogeneous and plastic nature of glioma tumor cells and their interactions with the microenvironment, although quantitative data are still largely missing. Here, we used high-dimensional, multiplexed immunohistochemistry to map the spatial, single-cell tissue architecture of 31 pediatric glioma samples covering 9 histologic diagnoses. This novel approach allowed us to map the spatial distribution of the various tumoral subtypes, which typically occur in specific tumoral niches, and how these interact with their local immune-microenvironment. Finally, by aligning these findings to the clinical data of the patients and comparing these to adult glioblastoma, we are now able to more precisely describe the heterogeneous landscape of pediatric glioma at single-cell resolution.